Pull Marketing and Aida Methode to Increase Brand Awareness and Interest - Cahyani, Maulia Endah; Hussein, Ananda Sabil (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2025)
This problem-solving research was motivated by the low level of brand awareness and customer interest in Kos Pak Mahfud, a women-only boarding house business located in Tegalgondo Village, Malang Regency. The business has relied solely on traditional marketing methods, resulting in unoccupied rooms and financial losses. This study aims to design and examine the implementation of a pull marketing strategy integrated with the AIDA method (Awareness, Interest, Desire, Action) to increase brand awareness and customer interest. The marketing strategy was formulated based on in-depth interviews with relevant informants. The developed marketing content was then tested on two sample groups: one group exposed to advertisements and a control group that was not exposed. The data were collected using Likert-scale questionnaires and analyzed to identify any significant differences in terms of awareness level and interest between the groups.